2007
DOI: 10.1097/01.prs.0000260730.43870.1b
|View full text |Cite
|
Sign up to set email alerts
|

Closed Reduction, Open Reduction, and Endoscopic Assistance: Current Thoughts on the Management of Mandibular Condyle Fractures

Abstract: The management of fractures of the mandibular condyle continues to be controversial. This is in part attributable to a misinterpretation of the literature from decades prior, a lack of uniformity of classification of the various anatomical components of the mandibular condyle, and a perceived potential to cause harm through the open approach based in part on the surgeon's lack of a critical examination of the literature. This review explores the key historical articles that deal with the management of mandibul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 66 publications
(79 reference statements)
0
31
0
2
Order By: Relevance
“…An endoscopically assisted intraoral approach with open reduction and internal fixation is becoming popular and these procedures show promising results 11,26 .…”
mentioning
confidence: 99%
“…An endoscopically assisted intraoral approach with open reduction and internal fixation is becoming popular and these procedures show promising results 11,26 .…”
mentioning
confidence: 99%
“…Many studies have reported that surgical treatment with open reduction and rigid fixation leads to significantly better results than conservative management of condylar fractures [6][7][8][9][10][11][12][13]. With the exception of undisplaced, intracapsular fractures and fractures in pediatric patients younger than 12 years of age [14][15], most mandibular condylar fractures should be treated with open reduction and rigid fixation.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of undisplaced, intracapsular fractures and fractures in pediatric patients younger than 12 years of age [14][15], most mandibular condylar fractures should be treated with open reduction and rigid fixation. Points to be clarified regarding surgical treatment, is how many fixation devices should be used [6], and the choice of approach for treating condylar fractures. The ideal surgical approach should be the least invasive method available, allow comfortable and easy solution to the surgical problem, be versatile, allow satisfactory vision, have the lowest rate of surgical complications, and be easily performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following two consensus meetings 1,2 in which researchers have had only limited agreement on an optimal treatment strategy in adults 3 subject to more than six classification proposals in the past 80 years, 4 the treatment of mandibular condyle fractures still remains a controversial topic in maxillofacial traumatology. 5 Mandibular condyle fractures account for 17.5 -52% of all mandibular fractures.…”
Section: Introductionmentioning
confidence: 99%